2020
DOI: 10.1242/bio.049692
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent degeneration of an identified adult leg motor neuron in a Drosophila SOD1 model of ALS

Abstract: Mutations in superoxide dismutase 1 (SOD1) cause familial Amyotrophic lateral sclerosis (ALS) in humans. ALS is a neurodegenerative disease characterized by progressive motor neuron loss leading to paralysis and inevitable death in affected individuals. Using a gene replacement strategy to introduce disease mutations into the orthologous Drosophila sod1 (dsod1) gene, Here, we characterize changes at the neuromuscular junction using longer lived dsod1 mutant adults. Homozygous dsod1H71Y/H71Y or dsod1null/null f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Studies in Drosophila and in mice demonstrated that expression of human SOD1 in motor neurons reduced ROS activity, leading to longevity ( Parkes et al, 1998 ; Missirlis et al, 2001 ). Further studies in flies demonstrated that the enzymatic activity of human SOD1 is not required for its toxicity: In fact, homozygous inactive SOD1 mutants (G85R, H48R, and H71Y) expression in dSOD1 null flies results in neurodegeneration, motor defects, and shortened life span, suggesting that these phenotypes are associated to SOD1-mutations rather than SOD1 activity ( Şahin et al, 2017 ; Agudelo et al, 2020 ). Expression of mutants SOD-1 results in deposition of protein aggregates visible in neurons, glia and in skeletal muscles in both mice-of ALS and cells from ALS patients ( Dirren et al, 2015 ).…”
Section: Neurodegenerative Proteinopathies or (Pps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Drosophila and in mice demonstrated that expression of human SOD1 in motor neurons reduced ROS activity, leading to longevity ( Parkes et al, 1998 ; Missirlis et al, 2001 ). Further studies in flies demonstrated that the enzymatic activity of human SOD1 is not required for its toxicity: In fact, homozygous inactive SOD1 mutants (G85R, H48R, and H71Y) expression in dSOD1 null flies results in neurodegeneration, motor defects, and shortened life span, suggesting that these phenotypes are associated to SOD1-mutations rather than SOD1 activity ( Şahin et al, 2017 ; Agudelo et al, 2020 ). Expression of mutants SOD-1 results in deposition of protein aggregates visible in neurons, glia and in skeletal muscles in both mice-of ALS and cells from ALS patients ( Dirren et al, 2015 ).…”
Section: Neurodegenerative Proteinopathies or (Pps)mentioning
confidence: 99%
“…SOD1 is involved in protein misfolding, and it is necessary for neuronal health ( Şahin et al, 2017 ; Agudelo et al, 2020 )…”
Section: Introductionmentioning
confidence: 99%
“…A number of fly models have been generated looking at SOD1 function in disease development. Both gain and loss of function models have been generated, as it is still a matter of debate whether ALS caused by SOD1 mutations is due to a gain or loss of function of the protein ( Mockett et al, 2003 ; Şahin et al, 2017 ; Agudelo et al, 2020 ).…”
Section: Fly Models Of Frontotemporal Dementia and Amyotrophic Lateral Sclerosis And Their Role In Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Drosophila Sod loss-of-function mutants exhibit elevated levels of reactive oxygen species (ROS) combined with a drastically shortened adult lifespan (median ~11 d. vs 50 d. for wild-type flies at 25 °C, Phillips et al, 1989) and reduced locomotor ability in larvae (Şahin et al, 2017) and adults (Ruan & Wu, 2008). Coupled with these longevity and behavioral phenotypes, several neuromuscular deficits have recently been identified in Sod loss-of-function mutants including deranged nerve and synapse morphology in larvae (Milton et al, 2011) and adults (Agudelo et al, 2020; Şahin et al, 2017), as well as disrupted neurotransmission along the giant-fiber (GF) jump-and-flight escape circuit (Iyengar et al, 2020; Iyengar, 2016; Ruan, 2008). Given the striking phenotypes, a question that arises is: To what extent the straightforward assumption holds that aspects of the Sod phenotypes can be recapitulated by pharmacologically induced oxidative stress?…”
Section: Descriptionmentioning
confidence: 99%